Upaya Meningkatkan Hasil Belajar IPAS Materi Wujud Zat dan Perubahannya melalui Media Video dan Benda Konkret - Wulandari, Diana Rizki Avita; Widiyatmoko, Wahyu (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
The purpose of this study is to enhance the learning outcomes of class IV SD Muhammadiyah 4 Surakarta students studying the natural and social sciences. Concrete objects and video media are the research materials used in